Pengaruh Kualitas Penanganan Delay dan Kompensasi terhadap Kepuasan Penumpang di Bandar Udara Internasional Halim Perdanakusuma - Melani Indah Cahyani; Dhiani Dyahjatmayanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Flight delays are a critical issue in the aviation industry, often directly impacting passenger experience and satisfaction. This study aims to analyze the extent to which the quality of delay handling (covering aspects such as communication, responsiveness, and facility support) and the quality of compensation (compliance with regulations, timeliness, and relevance) influence the level of passenger satisfaction at Halim Perdanakusuma International Airport (HLP). The research focuses on commercial flight passengers who have experienced delays at the airport as the study's respondents. The research method used is quantitative, with data collection conducted through questionnaires distributed to 400 respondents. Data were analyzed using multiple linear regression tests, including partial tests (t-test), simultaneous tests (f-test), and the coefficient of determination. The results show that: (1) the quality of delay handling has a significant effect on passenger satisfaction (sig. 0.000); (2) the quality of compensation has a significant effect on passenger satisfaction (sig. 0.000); (3) both variables simultaneously have a significant effect on passenger satisfaction (sig. 0.000); and (4) the coefficient of determination is 81.9%, indicating that the quality of delay handling and compensation together influence passenger satisfaction by 81.9%.